Test-retest reliability of the net joint power transferred by the lower limbs during walking in healthy men - Daniel Jandačka; Jaroslav Uchytil; Zdeněk Svoboda; Milan Elfmark; Miroslav Janura (Palacky University, 2013)
OBJECTIVE: To determine the reliability of the measurement of net joint power during repeated gait measurements within one day and between two different measurement days. METHODS: Thirty able-bodied men who underwent repeated gait measurements within a day and between days participated in this research. An acceptable trial was one in which the participant complied with the range of walking speed 1.45 m/s ± 5%. Three-dimensional angles, angular velocities, net moments of force and net power for the ankle, knee and hip joints were determined using external passive reflective markers, an 8-camera motion analysis system and two force plates. RESULTS: This study presents the patterns of the net power in the fundamental joints of the lower limbs in young healthy men at standard gait velocity. Intraclass correlation coefficients for net joint power measure reached values in the range of .70 to .89 on the first day, from .69 to .86 on the second day, and from .67 to .83 in total. CONCLUSION: The reliability of the measurement of the peak net joint power within one day and between the two measurement days was evaluated as satisfactory. The study provides the value of minimal detectable change for the peak net power of the lower limb in the sagittal plane during gait. The net joint power appears to be a reliable measure and could be used in practice.